Vaccines against human papillomaviruses - a major breakthrough in cancer prevention - Vonka, Vladimír; Hamšíková, Eva (Central European Journal of Public Health, 2007)
Carcinoma of the cervix (CaCer) is the second most frequent malignancy in women on a global scale. Epidemiological studies carried out at the beginning of the second half of the 20th century showed that CaCer was of infectious nature and that its agent was transmitted by sexual intercourse. For some 15 years, herpes simplex virus type 2 (HSV2), the genital herpes virus, was suspected to be the etiological agent. This hypothesis was disproved just in the time when the first convincing evidence that the agents of the disease were human papillomaviruses (HPVs) was produced. Copious new findings obtained during the 1980's and 1990's unequivocally confirmed that HPVs were the causative agents. The most dangerous among the over 100 HPV types are types 16 and 18, which together account for over 70% of CaCer cases and very likely also for most of the other malignancies of the anogenital region and the oropharynx. Extensive research of the HPV biology and immunology enabled the development of vaccines based on the s.c. virus-like particles (VLP) prepared by genetic engineering. At present, there is one HPV vaccine on the market; it contains, besides types 16 and 18, also types 6 and 11, the causative agents of certain benign tumours of the genital area and of the larynx. A new vaccine, comprising types 16 and 18 only, the product of another firm, is to appear on the market soon. Both vaccines have already been tested in extensive clinical trials. They are nearly 100% effective, only very weakly reactogenic and they undoubtedly belong among the most perfect vaccines ever produced. The darker side of the anti-HPV vaccines is their high price, the fact that the highest benefits they bring will only become evident in 20 or 30 years, and that they do not afford protection against all oncogenic HPVs. It is therefore imperative that organized cytological screening be continued: it is destined to remain the main instrument of CaCer prevention for several decades. With all probability also other types of vaccine are under development, viz. VLP-based vaccines, whose range of applicability will be wider than that of the present preventive vaccines, as well as vaccines that will, hopefully, be able to inhibit already progressing infection or will be utilizable in CaCer immunotherapy.
Keywords: Child; vakcíny proti papilomavirům; Humans; lidé; Alphapapillomavirus; mladiství; Papillomavirus Vaccines; Female; Male; Uterine Cervical Neoplasms; Adult; Papillomavirus Infections; mužské pohlaví; Mass Vaccination; infekce papilomavirem; ženské pohlaví; hromadná vakcinace; dospělí; dítě; nádory děložního čípku; Adolescent